Effect of Perceived Brand Foreignness on Perceived Quality and Purchase Intention of â€œMake Overâ€ Cosmetic - admin, Nopiati B12112003 (Jurnal Manajemen Update, 2016)
The used of Perceived Brand Foreigness strategyasÂ  aÂ  productÂ  namingÂ  strategy isÂ  veryÂ  popular.Â  Perceived Brand Foreignness (PBF) refers to a consumerâ€™s perception that a brand is come from overseas or non-local origin (BatraÂ  et.Â  allÂ  2000;Â  LingÂ  2008).Â  In Indonesia, this strategy has been a trend since some decades ago. As the implications, there are a lot of products on the market using foreign brand names, despite the fact that these products are local products that made in Indonesia. Kapferer (1997) suggests that consumers may prefer foreign brands because of the higher prestige that offered by the brand. The purpose of this study is to measure the effect of Perceived Brand Foreignness, Perceived Quality and Purchase Intention. The object that used in this research is â€œMake Overâ€ cosmetic. To reached the purpose of this reaseach the data was collectedÂ  through 100 questionnaires and using SmartPLS statistical software to test the hypothesis, the result shows that the effect of Perceived Brand Foreignness on Purchase Intention of â€œMake Overâ€ cosmetic is fully mediated by Perceived Quality. Keywords: Perceived Brand Foreignness, Perceived Quality, Purchase intention